The Influence of Work Environment, Work Motivation, And Career Development on Private Vocational School Teacher Performance - Dwi Lestari; Nina Fapari Arif; Meirani Harsasi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research aims to analyze the influence of the work environment, work motivation, and career development on teacher performance at Private Vocational High Schools (SMK) in Cepu District, Blora Regency. Teacher performance is a crucial aspect in improving the quality of education, especially in vocational schools which are required to produce work-ready graduates. This research uses a quantitative approach with survey methods. The population in this study were all teachers in three private vocational schools in Cepu, with a total of 139 respondents obtained through the census method. Data collection was carried out through a closed questionnaire with a five-point Likert scale covering four main variables. Data analysis was carried out using multiple linear regression using the latest version of SPSS. The research results show that the three independent variables, namely work environment, work motivation, and career development, simultaneously or partially have a positive and significant effect on teacher performance. Work motivation is the variable that most dominantly influences teacher performance compared to the other two variables. These findings have the implication that efforts to improve teacher performance must be focused on improving the work environment, providing incentives and recognition to increase motivation, as well as structured career development. This research also emphasizes the importance of managerial strategies and educational policies that support the sustainability of teacher professionalism in private schools. Thus, it is hoped that the results of this research can become a reference for school management and policy makers in improving the quality of education in developing areas such as Cepu.